Therapeutic Assessment of Cytochrome C for the Prevention of Obesity Through Endothelial Cell-targeted Nanoparticulate System - Hossen, Md. Nazir (Nature Publishing Group, 2013)
Because the functional apoptosis-initiating protein, cytochrome C (CytC) is rapidly cleared from the circulation (t(1/2) (half-life): 4 minutes), it cannot be used for in vivo therapy. We report herein on a hitherto unreported strategy for delivering exogenous CytC as a potential and safe antiobesity drug for preventing diet-induced obesity, the most common type of obesity in humans. The functional activity of CytC encapsulated in prohibitin (a white fat vessel-specific receptor)-targeted nanoparticles (PTNP) was evaluated quantitatively, as evidenced by the observations that CytC-loaded PTNP causes apoptosis in primary adipose endothelial cells in a dose-dependent manner, whereas CytC alone did not. The delivery of a single dose of CytC through PTNP into the circulation disrupted the vascular structure by the targeted apoptosis of adipose endothelial cells in vivo. Intravenous treatment of CytC-loaded PTNP resulted in a substantial reduction in obesity in high-fat diet (HFD) fed wild-type (wt) mice, as evidenced by the dose-dependent prevention of the percentage of increase in body weight and decrease in serum leptin levels. In addition, no detectable hepatotoxicity was found to be associated with this prevention. Thus, the finding highlights the promising potential of CytC for use as an antiobesity drug, when delivered through a nanosystem.